Mechanisms linking obesity, genomic instability and the radioresponse in oesophageal adenocarcinoma - Mongan, Ann Marie (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Surgery, 2014)
The increasing incidence of oesophageal adenocarcinoma (OAC) parallels the rapidly rising incidence of obesity. OAC is an exemplar model of obesity-associated cancer, with an increasing focus on the role of visceral adipose tissue (VAT). OAC confers a poor prognosis with five year survival of 20-40% in locally advanced diseased The current standard of care involves neoadjuvant chemoradiotherapy (NA-CRT). Tumour response to NA-CRT is the best predictor of survival, but resistance to therapy remains a significant clinical problem with only 15-30% of patients achieving a complete pathological response (pCR). The identification of biomarkers and molecular mechanisms of radioresistance would be of substantial clinical benefit, and is critical for improving the efficacy of treatment. Obesity is associated with the pathogenesis and progression of OAC, but the interaction between obesity and treatment response is unknown. Genomic instability is a hallmark of cancer associated with obesity. We hypothesised that genomic instability events are implicated In the interaction between obesity and the radioresponse in OAC.
Keywords: Surgery, Ph.D.; Ph.D. Trinity College Dublin